Transfer of dechlorane plus between human breast milk and adipose tissue and comparison with legacy lipophilic compounds. (October 2020) - Pan, Hai-Yan; Li, Ji-Fang-Tong; Li, Xing-Hong; Yang, You-Lin; Qin, Zhan-Fen; Li, Jin-Bo; Li, Yuan-Yuan
Abstract: In this study, levels of dechlorane plus (DP) in breast milk and matched adipose tissue samples were measured from 54 women living in Wenling, China. Polybrominated diphenyl ethers (PBDEs) and polychlorinated biphenyls (PCBs) were measured simultaneously for comparison. The levels of ∑DPs/∑PBDEs varied from less than one to several dozens of ng g −1 lipid weight (lw) in matrices and the levels of ∑PCBs varied between several to hundreds of ng g −1 lw. In the same matrix, ∑DPs and ∑PCBs/∑PBDEs showed a significant relationship ( p  < 0.05), indicating that they shared common sources. Accordingly, there was a strong association of lipid-adjusted concentrations of individual compounds (BDE-209 excluded) between matrices ( p  < 0.001), suggesting that breast milk could be a proxy for adipose tissue in human bioburden monitoring of these compounds. The predicted lipid-adjusted milk/adipose ratios varied from 0.62 to 1.5 but showed significant differences ( p< 0.001) between compounds, suggesting a compound-specific transfer between milk lipids and adipose tissue lipids. Specifically, the milk/adipose ratios for syn -DP and anti -DP (−1.40 and 1.3, respectively) were significantly higher than those of CB congeners and hexa/hepta-BDE congeners ( p  < 0.05). In addition, unlike PCBs/PBDEs (excluding BDE-209), DP's hydrophobicity might not be responsible for its preferable distribution in milk lipids. Instead, the interaction with nonlipid factors played a key role. The fraction of anti -DP between the two kinds of matrices was not significantly different, suggesting that the biochemical transfer processes may not be efficient enough to distinguish DP isomers. Nevertheless, the congener patterns of PCBs/PBDEs gave a clue about the compound-specific transfer between milk and adipose tissue. To our knowledge, this is the first to report the relationships of DP between adipose tissue and breast milk. These results could provide useful and in-depth information on biomonitoring of DP and facilitate the understanding of the accumulation and excretion potentials of DP and its distribution-related mechanism in humans. Highlights: Breast milk was a proxy of adipose tissue in biomonitoring human body burden of DP. A significant difference existed in DP concentrations between milk/adipose tissue lipids. Nonlipid factors might significantly impact on the milk-adipose partitioning of DP. In contrast to some most persistent lipophilic compounds, DP was easier to be excreted by milk route. Stereo-selectivity of DP did not occur during the adipose-milk transfer process. Abstract : The main findings in this manuscript: Transfer of DP between milk lipids and adipose tissue lipids showed a significant difference from that of legacy lipophilic compounds. This might be due to the interaction of DP with nonlipid factors in the blood.